2020
DOI: 10.2147/cmar.s234688
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Value of Geriatric Nutritional Risk Index in Evaluating Postoperative Complication Risk and Long-Term Prognosis in Elderly Colorectal Cancer Patients</p>

Abstract: The geriatric nutritional risk index (GNRI) has been reported as a useful tool for predicting the prognosis of many diseases; however, there is currently little research on the relationship between GNRI and outcomes in elderly colorectal cancer (CRC) patients. This study aimed to explore the value of GNRI in evaluating postoperative complication risk and long-term prognosis in elderly CRC patients. Patients and Methods: The medical records of 230 CRC patients aged≥65 years who underwent surgery between January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 33 publications
(34 reference statements)
0
47
0
Order By: Relevance
“…Seven of the studies lacked relevant outcomes. Therefore, our meta-analysis included nine studies involving 2,153 patients [ 10 , 12 , 14 , 19 24 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven of the studies lacked relevant outcomes. Therefore, our meta-analysis included nine studies involving 2,153 patients [ 10 , 12 , 14 , 19 24 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies were from Japan, and two studies were from China. Two studies reported GC [ 19 , 22 ], three studies reported ESCC [ 14 , 20 , 21 ], two studies reported CRC [ 10 , 12 ], one study reported colorectal liver metastasis (CRLM) [ 24 ], and one study reported pancreatic ductal adenocarcinoma (PDAC). In addition, four studies reported postoperative complications, eight studies reported OS, two studies reported RFS, and two studies reported DFS and CSS, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CONUT score, calculated based on albumin concentration, total cholesterol concentration and total lymphocyte count, is an effective and easy screening tool for evaluating immune-nutritional status. Albumin concentration is one of the most common parameters for assessing nutritional status, and albumin reduction is thought to be related to systemic inflammation affecting catabolism and anabolism of liver cells 18 . Hypoalbuminemia also may reduce patients' tolerance to surgery, leading to poorer prognosis 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its simple calculation, it has been gradually applied in the prognosis evaluation of various chronic diseases. GNRI has prognostic value in patients with esophageal cancer, [ 10 ] hepatocellular carcinoma, [ 11 ] colorectal carcinoma, [ 12 ] and non-small-cell lung carcinoma. [ 13 ] Lee et al, [ 7 ] found that GNRI is associated with the prognosis of patients with sepsis, and that patients with a lower GNRI had higher mortality rates.…”
Section: Discussionmentioning
confidence: 99%